Decolorization and detoxification of textile effluent by immobilized laccase-ACS into chitosan-clay composite beads using a packed bed reactor system: An ecofriendly approach. (June 2022) - Mehandia, Seema; Ahmad, Shabeer; Sharma, S.C.; Arya, Shailendra Kumar
Abstract: Immobilized laccase mediator system utilizing natural mediator is the best choice to deal with color based wastewater. In the present study, a bacterial laccase from Alcaligenes faecalis XF1 was immobilized into chitosan-clay composite beads (CCB-L) by physical entrapment method and resulted in 88.4% of immobilization yield. No leakage of enzymes was observed during washing and storage of beads. FTIR and EDX analysis of CCB-L confirmed the immobilization of laccase. Laccase and acetosyringone (ACS, a natural laccase mediator) were co-immobilized into chitosan-clay composite beads to form an immobilized laccase mediator system (CCB-L-ACS). CCB-L-ACS showed 78% decolorization of textile effluent through the packed bed reactor system (PBRS). UV-VIS spectrum analysis also confirmed the decolorization of effluent. Along with color, BOD and COD levels of the treated samples are also reduced to 91% and 87% respectively. The toxicity of the treated sample was evaluated by conducting a micro-toxicity assay using three different microbial species viz. E . coli, Bacillus subtilis and Saccharomyces cerevisiae . A substantial decrease in toxicity was recorded after treatment of effluent with CCB-L-ACS. All these observations indicate that the developed immobilized laccase mediator system (CCB-L-ACS) can be used for the treatment of dye based industrial wastewater. Graphical abstract: Unlabelled Image Highlights: Laccase and ACS were co - immobilized into CCB Beads to form CCB-L-ACS. CCB-L-ACS showed 78% decolorization of textile effluent through PBRS. BOD and COD levels of treated samples reduced by 91% and 87%. A significant decrease in toxicity of effluent after treatment.